Effects of a Grapevine Shoot Extract Containing Resveratrol and Resveratrol Oligomers on Intestinal Adenoma Development in Mice: In Vitro and In Vivo Studies. Issue 2 (9th January 2018) - Empl, Michael T.; Cai, Hong; Wang, Shan; Junginger, Johannes; Kostka, Tina; Hewicker‐Trautwein, Marion; Brown, Karen; Gescher, Andreas J.; Steinberg, Pablo
Abstract : Scope: Evidence suggests that the dietary consumption of plant extracts containing polyphenols might help prevent the onset of cancers of the gastrointestinal tract. In the present study, the chemopreventive and antiproliferative efficacy of a grapevine shoot extract (Vineatrol®30) containing resveratrol and resveratrol oligomers is investigated in vivo and in vitro. Methods and results: The in vivo study is performed using Apc Min mice on a high‐fat diet, which represents a model of human adenomatous polyposis, while the potential of the extract as well as some of its isolated constituents to inhibit intestinal adenoma cell proliferation in vitro is investigated using APC10.1 cells derived from an Apc Min mouse. Vineatrol®30 at a low (2.3 mg kg –1 diet) or high dose (476 mg kg –1 diet) reduces the adenoma number in male and adenoma volume in female animals. Furthermore, Vineatrol®30 as well as resveratrol and two resveratrol tetramers compromise the expansion of APC10.1 cells by reducing cell number, inducing cell cycle arrest, cellular senescence, and apoptosis. However, except for the extract, none of the isolated resveratrol oligomers is more efficacious than resveratrol in these cells. Conclusion: Vineatrol®30 may merit further investigation as a potential dietary gastrointestinal cancer chemopreventive agent in humans. Abstract : Two doses (2.3 and 476 mg kg –1 diet) of a commercially available grapevine shoot extract containing resveratrol and resveratrol oligomers significantly reduced the adenoma number and volume in male and female Apc Min mice, respectively. Moreover, the extract as well as some of its isolated constituents prevented the expansion of adenoma‐derived cells in vitro by reducing proliferation, inducing cell cycle arrests, cellular senescence, and apoptosis. The extract may therefore be considered for further investigation as a potential dietary cancer chemopreventive agent.